First Class Objects and Indexes for Chant Manuscripts - Barton, L; Jeavons, P; Caldwell, J (2007)
We discuss a crucial part of infrastructure for the Web-delivery of medieval chant resources. Although widely accepted by software professionals, the distributed-content model is sharply opposed by some chant scholars. We advocate for a paradigm of the Web as a massive database where each "first class object" acts like a record; metadata about, and links to such objects are compiled in virtual libraries. Scholarly-edited indexes determine which objects are in libraries, and unreliable content is excluded. Special metadata ontologies can be defined without modifying the primary content. Copyright 2007 ACM.